2000
DOI: 10.1177/136346150003700201
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Contributions to Understanding Racism

Abstract: This article reviews the theoretical contributions of psychiatrists to understanding racism. Racism is poorly understood because it is a tool of socio-economic oppression and it serves those in power to obscure its nature. Confounding factors are examined from several perspectives including coercive behaviors characteristic of unequal relationships, ethnocentric blindness, ignorance about socio-economic oppression and the racialization of poverty. The damaging effects of racism on physical and mental health ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 90 publications
0
3
0
1
Order By: Relevance
“…Structural racism or the “ways in which societies foster discrimination through mutually reinforcing inequitable systems[ 35 ]” can complicate mental health disparities. A general mistrust of health systems is based on the historical mistreatment of Blacks in psychiatric care[ 36 ]. To this extent, the American Psychiatric Association issued a public apology about their role in Blacks’ historical injustices acknowledging their influence in inequitable practices, including the misdiagnosis of schizophrenia in this population[ 37 ].…”
Section: Ethnic Disparitiesmentioning
confidence: 99%
“…Structural racism or the “ways in which societies foster discrimination through mutually reinforcing inequitable systems[ 35 ]” can complicate mental health disparities. A general mistrust of health systems is based on the historical mistreatment of Blacks in psychiatric care[ 36 ]. To this extent, the American Psychiatric Association issued a public apology about their role in Blacks’ historical injustices acknowledging their influence in inequitable practices, including the misdiagnosis of schizophrenia in this population[ 37 ].…”
Section: Ethnic Disparitiesmentioning
confidence: 99%
“…Among ethnic groups, Pacific peoples have the lowest income (Miller et al 1997;Ministry of Pacific Island Affairs 1999) and the highest rate of unemployment in New Zealand (Ministry of Pacific Island Affairs 1999). In keeping with the elders' beliefs, it has been shown that poverty doubles the risk of developing mental illness, decreases the life span, and increases the rate of death from all causes (Moore 2000). Poverty leads to problems with transportation and buying medication, which interfere with effective treatment of Samoan New Zealanders (Esera 2001;Miller et al 1997;Ministry of Health 2002).…”
Section: Stressors Specific To Samoan New Zealandersmentioning
confidence: 99%
“…Tal foi uma atitude corriqueira na história da psiquiatria, considerar psicopatológica qualquer manifestação fora dos padrões ordinários. É um fato reconhecido o quanto essa postura impediu uma melhor compreensão da mente humana e deu origem a atitudes discriminatórias (Almeida e Almeida, 2000;Moore, 2000).…”
Section: Evitar "Patologizar" O Diferente De "Anômalo"unclassified